Acara Petualangan Televisi Sebagai Media Pembentukan Karakter Pencinta Alam Bagi Pemuda Era Migrasi Penyiaran Digital - A’lam, Naufal Nur; Abdurrazaq, Muhammad N. (SALAM: Jurnal Sosial dan Budaya Syar-i, 2020)
This study examines the level of relevance of television programs as a medium for supporting nature-loving character formation for youth in the era of digital broadcasting migration in the midst of an assessment that TV is actually considered damaging to character with the aim of knowing whether TV is still a relevant factor as a media supporting character formation. nature lovers for youth, as well as how to practice and apply the attitude of nature lovers after watching TV adventure programs in their daily lives. This research method uses qualitative-descriptive research methods with a phenomenological approach. The sample of this study amounted to 9 informants who met the criteria (purposive sampling). The results of the study, based on the Trend Dimensions of Factor X, show that there is still a strong level of relevance of TV with a percentage of 67% as a media to support the formation of nature lover characters for youth in the era of digital broadcasting migration through adventure programs, but in terms of duration, currently youth aged 17-33 watching TV adventure programs has decreased with a percentage of rarely watching 67%, in this digital era youths have turned to social media and digital platforms as supporting media for character building with a higher duration compared to watching TV, applying nature-loving attitudes and characters in life. Daily activities show that Actions for Caring & Conserving Nature with a percentage of 46% are the most common attitudes, followed by 25% Attitudes of Responsibility, Actions for Animal Cultivation 14%, Being an Activist in Nature 11%, and Caring for Humanity 4%.Keywords: TV Adventure Program, Nature Lover, Digital Broadcasting AbstrakPenelitian ini mengkaji tentang tingkat relevansi program acara televisi sebagai media pendukung pembentukan karakter pencinta alam bagi pemuda di era migrasi penyiaran digital di tengah-tengah penilaian bahwa TV justru dianggap merusak karakter dengan tujuan untuk mengetahui apakah TV masih menjadi faktor yang relevan sebagai media pendukung pembentukan karakter pencinta alam bagi pemuda, serta bagaimana praktek dan penerapan sikap karakter pencinta alam usai menonton program acara petualangan TV dalam kehidupan sehari-hari. Metode penelitian ini menggunakan metode penelitian kualitatif-deskriptif dengan pendekatan fenomenologis. Hasil dari penelitian, berdasarkan Dimensi Tren Faktor X menunjukkan bahwa masih adanya relevansi TV tingkat kuat dengan persentase 67% sebagai media pendukung pembentukan karakter pencinta alam bagi pemuda di era migrasi penyiaran digital lewat program petualangannya, namun secara durasi, saat ini pemuda usia 17-33 sudah berkurang menonton program petualangan TV dengan persentase jarang menonton sebesar 67%, di era digital ini pemuda sudah beralih ke sosial media dan platform digital sebagai media pendukung pembentukan karakter dengan durasi yang lebih tinggi dibandingkan dengan menonton TV, penerapan sikap dan karakter pencinta alam dalam kehidupan sehari-hari menunjukkan bahwa Aksi Peduli & Melestarikan Alam dengan persentase 46% menjadi sikap terbanyak, selanjutnya 25% Sikap Tanggung Jawab, Aksi Budidaya Hewan 14%, Menjadi Seorang Penggiat Alam Bebas 11%, dan Peduli Sosial Kemanusiaan 4% persentase-nya.Kata Kunci: Program Petualangan TV; Karakter Pencinta Alam; Migrasi Penyiaran Digital.